Spatial Distribution of Unique Biological Communities and Their Control Over Surface Reflectivity of the Stanley Glacier, Uganda - Uetake, Jun; Samyn, Denis; Anguma, Simon; Takeuchi, Nozomu (Frontiers in Earth Science, 2022)
Diverse microbes have been revealed to live in glaciers worldwide, however, only a few biological studies were dedicated to glaciers in tropical Africa, which are shrinking rapidly and are expected to disappear shortly. In this study, we carried out biological and glaciological field observations on Stanley Glacier, the largest glacier in the Rwenzori Mountains, Uganda, in Africa. Microbial aggregations, ranging from micrometer to centimeter in size, were found on the glacier surface and contained moss and Chlorophyta. Concentrations of total impurities on the glacier surface, including the microbial aggregations, varied spatially and decreased as altitude increased. The large microbial aggregations (larger than 4 centimeters) were found only at the glacier surface near the terminus and side margins, where the surface was less frequently covered with snow. It is also shown that the total organic matter on the glacier surface is determined by the timing of snow cover, which affects the quantity of solar radiation reaching the glacier ice surface. Furthermore, the concentration of total impurities was negatively correlated with surface reflectivity, thereby revealing their potential role in albedo reduction at the glacier surface through positive feedback between enhanced meltwater and increased biological growth.